Celebrity worship pada perempuan dewasa awal penggemar K-pop: bagaimana peran kesepian? - Suryaningsih, Endah; Pratitis, Niken Titi; Arifiana, Isrida Yul (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Celebrity worship is excessive idolization behavior, this behavior occurs a lot in adolescents and will decline in adulthood but some studies have found that Celebrity worship still occurs in early adulthood. This study aims to determine the relationship between loneliness and celebrity worship in early adult female K-pop fans. This study used quantitative research methods involving 100 adult female K-pop fans. The research technique used in sampling used accidental sampling. The measuring instrument in this study used a 25-item loneliness scale and a 20-item celebrity worship scale. The results of the analysis show that the hypothesis is rejected and there is a significant negative relationship between loneliness and Celebrity worship in adult female K-pop fans. In conclusion, loneliness and celebrity worship are not related, which means that if individuals have a low level of loneliness, the tendency for celebrity worship behavior is high. Vice versa, the higher the level of individual loneliness, the lower the tendency of celebrity worship behavior. Celebrity worship adalah perilaku pengidolaan yang berlebihan, perilaku tersebut banyak terjadi pada remaja dan akan menurun pada usia dewasa namun beberapa penelitian ditemukan bahwa Celebrity worship masih terjadi pada masa dewasa awal. Penelitian ini bertujuan untuk mengetahui hubungan antara kesepian dengan celebrity worship pada perempuan dewasa awal penggemar K-pop. Penelitian ini menggunakan metode penelitian kuantitatif dengan melibatkan 100 orang perempuan dewasa penggemar K-pop. Teknik penelitian yang digunakan dalam pengambilan sampel menggunakan accidental sampling. Alat ukur dalam penelitian ini menggunakan skala kesepian sebanyak 25 aitem dan skala celebrity worship sebanyak 20 aitem. Hasil analisis menunjukkan bahwa hipotesis ditolak dan terdapat hubungan negatif siginifikan antara kesepian dengan Celebrity worship pada perempuan dewasa penggemar K-pop. Kesimpulannya kesepian dan celebrity worship tidak berhubungan yang dapat diartikan apabila individu memiliki tingkat kesepian yang rendah maka kecenderungan perilaku celebrity worship tinggi. Begitu pula sebaliknya, semakin tinggi tingkat kesepian individu maka semakin rendah kecenderungan perilaku celebrity worship.